PENGARUH BRAND TRUST DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN DAN MINAT BELI ULANG IKAN SARDEN KALENG MEREK ABC DI KOTA PEKANBARU - , Jushermi, Muhammad Fajri , Sri Restuti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Throughout 2020 the whole world was shaken by Covid-19 where everyone was required to stay at home, as a result of this situation instant food became the choice of many people to meet their food needs, especially Indonesian people who chose canned sardines, especially the ABC brand. This study aims to determine how the influence of brand trust and perceived quality on purchasing decisions and repurchasing intention of canned sardines with the ABC brand in Pekanbaru City. This study uses quantitative research methods, to obtain primary and secondary data where data collection is carried out by conducting interviews, distributing questionnaires, observation and literature study with a population of 15 sub- districts of Pekanbaru City and a sample of 105 people. Using the Propotional Quota Sampling. jungpinang City as respondents, using the Non-Probability sampling Technique. The Data Analysis Technique Used In This Study Is Path Analysis The results of this study are that brand trust has a positive influence on purchasing decisions and perceived quality has a positive effect on purchasing decisions. Brand trust has an effect on purchasing decisions and repurchase intention, perceived quality has an effect on buying and repurchasing decisions on canned sardines with the ABC brand. It can be said that with the existence of brand trust and perceived quality provided by canned sardines with the ABC brand, consumers are sure to decide to buy the product and are interested in buying it again. It is hoped that the company will continue to maintain its reputation and improve product quality, such as improving the texture and providing detailed information on the product and carrying out even better promotions. Keywords: Brand Trust, Perceived Quality, Purchase Decision, Repurchase Intention